Pengaruh Kesadaran Metakognitif, Kemandirian Belajar dan Regulasi Diri Terhadap Hasil Belajar Biologi Peserta Didik Kelas XI SMA Negeri di Kabupaten Polewali Mandar - Ulfa Auliah Dwiyanti; Yusminah Hala; Andi Mu’nisa; Firdaus Daud; Nurhayati B (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to analyze the influence of metacognitive awareness, learning independence, and self-regulation on the biology learning outcomes of Grade XI students at state high schools (SMA Negeri) in Polewali Mandar Regency. The study employs a quantitative approach with an *ex post facto* design. The population consisted of 1,524 students, from which a sample of 228 students was selected using purposive sampling. Data were collected via Likert-scale questionnaires and multiple-choice tests, then analyzed using multiple linear regression. Simple regression analysis results indicate that metacognitive awareness significantly influences biology learning outcomes (significance value 0.000 < 0.05) with a contribution of 42.9%; learning independence significantly influences biology learning outcomes (significance value 0.000 < 0.05) with a contribution of 37.7%; and self-regulation significantly influences biology learning outcomes (significance value 0.000 < 0.05) with a contribution of 27.9%. Simultaneously, these three variables have a positive and significant effect on biology learning outcomes (significance value 0.000 < 0.05) with a contribution of 55.1%. Based on effective contribution, metacognitive awareness provided the largest contribution (26.2%), followed by learning independence (16.3%) and self-regulation (12.5%). These findings indicate that enhancing metacognitive awareness, learning independence, and self-regulation is crucial for improving students' biology learning outcomes, even though the current levels of these variables remain in the moderate category.